2018
DOI: 10.1007/s11252-017-0726-6
|View full text |Cite
|
Sign up to set email alerts
|

Buzzing on top: Linking wild bee diversity, abundance and traits with green roof qualities

Abstract: Green roofs are potentially valuable habitats for plants and animals in urban areas. Wild bees are important pollinators for crops and wild plants and may be enhanced by anthropogenic structures, but little is known about wild bees on green roofs in cities. This study investigates the effects of green roof qualities (floral resources, substrate character and depth, roof height and age) on wild bee diversity, abundance and traits (nesting type, sociality, pollen specialisation, body size) on green roofs in Vien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 43 publications
2
32
0
Order By: Relevance
“…This is true in our study where just four species account for almost three-fourths of all snails found. Also as found in many other invertebrate studies [5, 32], most of our green roof species are native, with a minority (at least three species) being invasive, broadly adapted non-native species.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This is true in our study where just four species account for almost three-fourths of all snails found. Also as found in many other invertebrate studies [5, 32], most of our green roof species are native, with a minority (at least three species) being invasive, broadly adapted non-native species.…”
Section: Discussionsupporting
confidence: 67%
“…In terms of species richness, our findings indicate that land snails on green roofs may be considerably less diverse than more mobile taxa. For example, [5] surveyed just nine green roofs in Vienna, Austria, and identified 90 wild bee species. A study of 17 green roofs in Switzerland found 161 highly dispersive beetle species [28].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For bees, green roofs support both social and solitary species, ground-or cavity-nesting, polylectic species [49,66,103], and species of varying body size (more small and medium sized bees in Chicago [80], but less small than medium or large bees in Toronto, [104]). Generalists (e.g., polyphagous) species were common among other arthropods as well [50], as were highly mobile [50,105]) and thermo-or xero-thermophilic species [50,76].…”
Section: Trends In Green Roof Functional Diversity and Patterns In Fumentioning
confidence: 99%
“…In terms of species richness, our findings indicate that land snails on green roofs may be considerably less diverse than more mobile taxa. For example, Kratschmer and others [5] surveyed just nine green roofs in Vienna, Austria, and identified 90 wild bee species. A study of 17 green roofs in Switzerland found 161 highly dispersive beetle species [27].…”
Section: Comparison To Other Green Roof Faunamentioning
confidence: 99%